Comprehensive Analysis of Al-Ahkam Al-Khomsah: Islamic Law Perspective and Contemporary Implementation - Suhaimis, Suhaimis; Saifullah, Saifullah; Kamal, Tamrin; Asmaret, Desi; Julhadi, Julhadi (LPPPIPublishing, 2025)
This journal article presents a comprehensive analysis of Al-Ahkam Al-Khomsah, a fundamental concept in Islamic jurisprudence that classifies actions into five legal categories: obligatory (wajib), recommended (mandub), permissible (mubah), disliked (makruh), and prohibited (haram). The study explores the traditional Islamic law perspective of these categories, which guide the ethical and legal conduct of Muslims. Additionally, the paper examines how these rulings are interpreted and applied in contemporary contexts, considering the challenges posed by globalization, technological advances, and social changes. The analysis highlights how Islamic scholars have adapted the understanding of Al-Ahkam Al-Khomsah to address modern issues, such as evolving social norms, new technological innovations, and legal systems. Through this exploration, the paper aims to provide a nuanced understanding of how Islamic law continues to shape both individual behavior and societal development in the modern world while remaining rooted in its classical principles. The findings underscore the dynamic nature of Islamic jurisprudence and its capacity to offer relevant guidance in addressing contemporary challenges.